TRAINING AS AN INSTRUMENT OF IMPROVING THE PSYCHOLOGICAL CLIMATE IN THE TEAM - Самойленко, Олена; Корнєєва, Олена (SWorldJournal, 2024)
The article offers training that is included in the program for improving interpersonal relations in the team.The purpose of the work was to develop a detailed plan of training for improving the psychological climate in female, male and mixed groups of